Penerapan Metode EOQ Pada Sistem Informasi Manajemen Stok Bahan Baku Ayam Broiler Berbasis Web - Sabrina Putri; Muhammad Dedi Irawan; Heri Santoso (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
The Economic Order Quantity (EOQ) method is an important inventory management to determine the optimal order quantity to minimize total inventory costs, including ordering costs, storage costs, and stockouts. Companies use technology to make data management easier. With the increasing demand for chicken meat, efficient raw material management is very important to reduce production costs and maintain chicken health. This study found problems faced by companies as a result of manual recording systems that are prone to errors and data loss. The study aims to improve the accuracy of feed management, reduce waste, and ensure proper nutrition for broiler chickens through the implementation of this system. The results of the implementation of this system show improvements in raw material efficiency analysis and stock monitoring. In addition to helping improve the productivity and sustainability of the broiler chicken farming industry, this study offers solutions for companies to overcome current management problems. The system uses the PHP programming language, the codeigniter framework and MySQL as a database.